ГЕНДЕРНЫЕ АСПЕКТЫ ФИЛОСОФИИ АЛЬ-ФАРАБИ: ЭТИКА, ОБРАЗОВАНИЕ И РОЛЬ ЖЕНЩИН В ОБЩЕСТВЕ - Сеитова, З.П. (SCIENCE and SOCIETY, 2025)
This article examines Al-Farabi’s views on the role of women in society, education, and ethics. His philosophical treatises, which emphasize the importance of women’s intellectual development and their active participation in social life, are analyzed. Special attention is paid to the influence of ancient philosophers, as well as the Islamic tradition, on the formation of the thinker’s views. The work is based on the analysis of primary sources and research by contemporary scholars.